(untitled) (Research, Society and Development, 2020)
In Brazil there are few studies about soy cultivation succeeding annual winter pastures. It was proposed in this work to evaluate the influence of the black oat seeding density and the management used on the agronomic characteristics and soybean productivity in succession. The experiment was conducted in a randomized block design in a scheme strip plots, with additional witness and four replications. The treatments consisted of two seeding densities of oat (40 and 60 kg ha-1) in strip A and different managements (without grazing, one grazing, and two grazing,) in strip B, in the winter period, in addition to the witness. In the summer, in the 2016/2017 harvest, the soybean planting was carried out (RR Nidera 5909). Plant population, plant height, stem diameter, number of pods per plant, number of grains per pod, number of grains per plant, mass of a thousand grains and soybean productivity were evaluated. The use of 40 kg ha-1 of black oat seeds for the western region of Paraná is indicated, as it does not promote changes in soybean productivity in succession and generates savings in the acquisition of seeds. The oat crop in the winter period in integrated agricultural production systems, regardless of seeding and management adopted, does not affect the productivity of the cultivated soybean crop is an excellent alternative for diversification of production on the farm.